BIJAK BERMEDIA SOSIAL DI ERA DIGITAL: EDUKASI UNTUK SANTRI DAARUL MUTA’ALIMIN TASIKMALAYA - Yana Handayah; Ulia Romdini; Yulia Isnawari (Yayasan Nusa Cendekia Global, 2025)
Social media is used as a platform for communication, interaction, and networking. This activity aims to raise awareness and ethics among students in using social media in the digital era and utilizing it to develop their talents. Environmental and family factors play a crucial role in guiding teenagers to understand its impact. The methods used include Technology Guidance (Bimtek), mentoring, supervision, and the involvement of parents and teachers to ensure the wise use of social media. As a result, students gain a better understanding of smart social media usage, including digital transactions, and increase their awareness of potential risks. Social media should be optimized for education and work, considering its fast accessibility. Information technology has both positive and negative impacts, depending on how each individual uses it.